<htm>Orchidaceae de um fragmento campestre em Ponta Grossa, Paraná, Brasil </htm> - Engels, Mathias Eric; Smidt, Eric de Camargo (Acta Biológica Paranaense, 2016)
<htm>Orchidaceae de um fragmento campestre em Ponta Grossa, Paraná, Brasil </htm>